Transforming the Northeast Tackling Backlogs in Basic Minimum Services and Infrastructural Needs High Level Commission Report to the Prime Minister - Planning Commission (Planning Commission, 1997)
In pursuance of the Prime Minister’s announcement of New Initiatives for the North Eastern Region made at Guwahati on October 27, 1996, a High Level Commission was appointed under the Chairmanship of Shri S P Shukla, Member, Planning Commission, with Shri B.G. Verghese, Fellow, Centre for Policy Research, New Delhi, Shri Sainghaka, Vice-Chairman, Planning Board, Mizoram, and Shri Jayanta Madhab, Chairman, North Eastern Development Finance Corporation, as Members Shri Darshan Kumar, Adviser, Planning Commission, was appointed as Secretary to the Commission.
Government of India, Planning Commission